Lenin from Latin America – Towards a reactivation of the marxism of political organisation and strategy - Sandoval Cordero, Mauricio (2021)
We are currently going through a civilisational crisis threatened by a possible collapse on a global scale,1 with varying socio-economic consequences in different parts of the world, further impacted by the ongoing health and climate crises as a result of the COVID-19 pandemic and the large-scale devastation repeatedly caused by hurricanes, flooding, droughts etc. At the time of writing, the overall situation in Latin America is one of intense socio-political effervescence marked by a series of acute conflicts in places like Bolivia, with the return to power of the Movimiento al Socialismo (MAS) a year after having been deposed by a coup d’etat; Chile, where a popular uprising and the demand for the re-writing of the dictatorial constitution of the Pinochet times is challenging the status quo; and countries like Colombia, Peru, Brazil, Guatemala and Costa Rica, among others, which have witnessed confrontations between repressive state forces and the popular masses.